1998
DOI: 10.1089/thy.1998.8.49
|View full text |Cite
|
Sign up to set email alerts
|

Prospective and Controlled Study of Ophthalmopathy After Radioiodine Therapy for Graves' Hyperthyroidism

Abstract: The effects of radioiodine (131I) therapy for hyperthyroidism on the ocular process of Graves' disease is controversial. In order to evaluate the outcome of ophthalmopathy after radioiodine therapy for thyrotoxicosis we studied prospectively 30 Graves' hyperthyroid patients, 22 submitted to radioiodine (131I) treatment (group A) and 8 treated with antithyroid drugs (group B). All patients were evaluated by clinical ophthalmologic examination, and ocular proptosis (OP) was measured with both a Hertel exophthalm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
6

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 27 publications
1
12
0
6
Order By: Relevance
“…Alguns estudos descreveram agravamento da doença ocular possivelmente secundário à liberação dos antígenos tireoidianos na circulação, favorecendo reação cruzada entre esses antígenos e fibroblastos da órbita, com infiltração da mesma pelas células T ativadas (60). No entanto outros autores observaram que o 131 I não influencia (61) tireoidismo, assim como a redução do volume glandular foi similar nos pacientes que utilizaram doses padronizadas de 131 I comparado com o uso de doses calculadas de forma mais elaborada.…”
Section: Iodo Radioativo Iodo Radioativounclassified
“…Alguns estudos descreveram agravamento da doença ocular possivelmente secundário à liberação dos antígenos tireoidianos na circulação, favorecendo reação cruzada entre esses antígenos e fibroblastos da órbita, com infiltração da mesma pelas células T ativadas (60). No entanto outros autores observaram que o 131 I não influencia (61) tireoidismo, assim como a redução do volume glandular foi similar nos pacientes que utilizaram doses padronizadas de 131 I comparado com o uso de doses calculadas de forma mais elaborada.…”
Section: Iodo Radioativo Iodo Radioativounclassified
“…In this last study, the course of the ophthalmopathy was worse after 131 I therapy than after subtotal thyroidectomy. Manso et al (26), in a prospective, nonrandomised study enrolling 22 patients, found no progression of the ophthalmopathy. The results of non-randomised studies, summarised in Fig.…”
Section: Introductionmentioning
confidence: 96%
“…Posteriormente, em trabalho complementar (52) demonstraram que a reposição precoce com T4 reduz a ocorrência de oftalmopatia após emprego de radioiodo. Estudo de nossa unidade, controlado, prospectivo e empregando mensurações objetivas, não demonstrou agravamento da oftalmopatia com o radioiodo comparado ao tratamento com anti-tiroideanos (53). Recentemente, porém, outro trabalho num grande número de pacientes, apresenta resultados diferentes, indicando piora da oftalmopatia com o emprego do iodo radioativo (54).…”
Section: Discussionunclassified